Ever widening circles of compassion - Koerner, Catherine (Australian Critical Race and Whiteness Studies Association, 2019)
This paper argues that Darwin’s work relied upon patriarchal white assumptions of entitlement to knowledge, their objects and the processes of knowledge production. It assumed an objective observer and fashioned their conquest of knowledge, knowledge production and the objects of knowledge to fit patriarchal white supremacist views. I posit that this materialist view has been promulgated as the only legitimate view, despite being debunked within quantum physics and quantum cosmology, and has led us to these dark times. The consequences risk the future of the planet and all its sentient inhabitants. However, Charles Darwin also posited in his meticulous observations that evolutionary development depends on ever-widening circles of compassion as the deepest primal instinct of all creatures – a view shared by First Nations peoples, such as Indigenous Australians colonised under Liberal/Neoliberal regimes and Tibetan (and others) colonised under Communist regimes. Neoliberalism has increased the intensity of consequences in Australia; however, this paper argues that the concept of a shared origin is the fundamental error about the nature of reality presented in metaphysical realism in triad with extractive possessive consumerism. The latter prioritises economic growth and hedonism and values only external happiness rather than a Eunomia understanding of wellbeing, where Eunomia refers to a general sense of inner wellbeing not caused by perceived external stimuli. CRAWS scholars can draw on ever widening circles of compassion as First Nation and critical ally scholars, educators and activists, to reorient our past understanding and present mindful embodiment for a fiercely compassionate future.